Missiology as a theological and academic discipline - Penner, Peter F. (Bogoslovskie razmyšlenija, 2018)
Missiology is a relatively young discipline in the faculty of theology and has often found its place in combination with other disciplines. The first part of the article offers an overview on missiology. Historically mission studies have been identified as pragmatical. But missiology has a history of academic research and claims an important role in theology. Today missiology offers different methodological approaches and a hermeneutical lens. But it also uses methods from other disciplines, especially as part of interdisciplinary studies. The second part of the article shows exemplary how missiology, on the one hand, applies methods, for example, from practical theology. But as one main ingredient in missiology, the contextual lens expands research in missiology beyond practical theology, as presented in the praxis cycle of Kritzinger. Missiology offers, in combination with other theological disciplines, similar possibilities and provides new perspectives in theological research.